Study of an Evaporation System for Sodium Hydroxide Solution - Rahman, Md Atikur; Khan, Nymul Ehsan (Journal of Chemical Engineering, 2010)
The textile industry in Bangladesh uses a substantial quantity of caustic soda (sodium hydroxide) to clean and prepare fabrics for dyeing. In all textile mills dealing with finishing, particularly with the mercerizing of cotton and mixed cotton fabrics, dilute caustic soda solutions come out as effluent from mercerizing unit. Caustic soda is expensive and its disposal without neutralization is unacceptable. A considerable amount of caustic soda can be saved if the dilute solution leaving the mercerizing step can be collected, concentrated and recycled. The concentration of the dilute caustic soda solution can be carried out by means of evaporation. A single effect evaporation system to concentrate the dilute sodium hydroxide solution was constructed and operated. The operating results confirm the economic viability of such recovery scheme. Journal of Chemical Engineering Vol.ChE 24 2006 35-36